Keberkesanan Perumahan Bantu Diri Di Skim Penempatan Semula. Nelayan Tanjung Dawai, Kedar - Shaari, Atan (2000)
Much have been said and done to overcome the problem of housing particularly at urban area. The theory of self-help housing has always link which other relevant programmes such as sites and services. In Kedah, one of the programme is The Resettlement Scheme for the fishermen. The combination of both factors in this scheme is not affected for the fishermen to build their own house by the scheme of self-help housing. The theory has not been proved yet. This research is aim to analyse the performance of self-help housing focusing on the element such as the affordability, building skills, minimum standard and the government function.